1988
DOI: 10.1111/j.1365-2621.1988.tb07784.x
|View full text |Cite
|
Sign up to set email alerts
|

Diacetyl and Acetaldehyde Concentrations During Ripening of Kefalotyri Cheese

Abstract: Diacetyl and acetaldehyde were determined during ripening of Kefalotyri cheese produced using two different lactic cultures (A: Streptococcus thermophilus + Lactobacillus casei, Sl cheese, B: Streptococcus thermophilus + Streptococcus diacetylactis + Streptococcus durans, S2 cheese). Diacetyl increased until the 60th day of ripening (2.49 and 1.62 ppm for Sl and S2 cheese, respectively) and until then was found in higher concentration in trials compared with control (0.91 ppm at 60 days). The possible contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The cheesemaking technology may vary in different places in Greece where Kefalotyri is produced [19,47]. Raw milk is used for its artisanal manufacture; however, nowadays, pasteurized milk is used for its production [24,[47][48][49][50][51][52][53].…”
Section: Kefalotyri Cheesementioning
confidence: 99%
“…The cheesemaking technology may vary in different places in Greece where Kefalotyri is produced [19,47]. Raw milk is used for its artisanal manufacture; however, nowadays, pasteurized milk is used for its production [24,[47][48][49][50][51][52][53].…”
Section: Kefalotyri Cheesementioning
confidence: 99%
“…This shows that D-erythrulose reductase also plays an important role in the liver. Dicarbonyl compounds such as diacetyl, a good substrate of the enzyme, are present in many everyday foods and beverages, such as alcoholic drinks (9, JO), milk (11), butter (12), buttermilk (13), cheese (14,15), and orange juice (16). Borders and Riordan reported that about 1 mM diacetyl modified arginine residues in proteins (17), which suggests that a high concentration of diacetyl may be toxic for animals.…”
Section: Substrate Specificity Of D-erythrulose Reductase-mentioning
confidence: 99%